ANALISA SIFAT MAGNETIK DAN IDENTIFIKASI KANDUNGAN PASIR SUNGAI KAMPAR PROVINSI RIAU - William Handerson; Salomo Sinuraya (Komunikasi Fisika Indonesia, 2020)
Research on the Analysis of Magnetic Properties and Content Identification of kampar River Sand Riau Province has been carried out. Sand samples taken in the Kampar River were then taken to  University of Riau instrumentation and magnetization laboratory to dry first, after which magnetic mineral separation was carried out using an Iron Sand Separator (ISS) . The next sample was measured its magnetic induction value using 2500 winding solenoids with currents (200, 400, 600, 800, 1000) mA with a fixed distance of 1 mm. The results showed that the magnetic susceptibility value for sand samples at point C was the highest value followed by the location of point B and point A with successive values of 13,767.96 x , 8,508.48 x  , and 8.008.10 x , and this value is included in the anti-ferromagnetic ilminite (FeTiO3) interval with a range of values (220-380000) x ,  . The results of the mass susceptibility value for the concentrate show that sand at the location of point C is the highest value followed by locations of points B and A with values of 13,969.70 x . 9,482.71 x .  and 6,441.25 x ., and this value is included in the inter ferromagnetic FeTiO3 ilminite interval with a range of values (46-8000 ) x .. X-Ray Fluorescence (XRF) test results for the Fe element have increased after ISS. Sand which is at point B has a greater percentage, followed by the locations of points A and C with values respectively 17.265%, 11.386% and 10.952%.